(5-2x)(4-x)-2x(x+6)=1-x 5x(x-8)-(5x-2)(x+1)=6x P.S желательно при решении x влево цифры вправо

(5-2x)(4-x)-2x(x+6)=1-x 5x(x-8)-(5x-2)(x+1)=6x P.S желательно при решении x влево цифры вправо
Гость
Ответ(ы) на вопрос:
Гость
[latex]1)\; \; (5-2x)(4-x)-2x(x+6)=1-x\\\\20-5x-8x+2x^2-2x^2-12x=1-x\\\\-25x+x=1-20\\\\-24x=-19\\\\x=\frac{-19}{-20}=\frac{19}{20}=0,95[/latex] [latex]2)\; \; 5x(x-8)-(5x-2)(x+1)=6x\\\\5x^2-40x-5x^2-5x+2x+2=6x\\\\-43x-6x=-2\\\\-49x=-2\\\\x=\frac{-2}{-49}=\frac{2}{49}\\[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы